Penerapan Kurikulum Merdeka Berdasarkan Teori Belajar Humanisme di Pendidikan Dasar - Safitri, Ulandari; Gistituati, Nurhizrah (Mitra PGMI: Jurnal Kependidikan MI, 2024)
This research is based on the assumption of a humanistic approach which views students as complete individuals who have their own uniqueness. The humanistic approach seeks to humanize humans and help them actualize themselves through various humanistic learning methods and strategies. The research method used is a descriptive method in the form of a literature review. Data collection by collecting articles, books, documents and other references related to the independent curriculum and humanistic theoretical views collected via Google Scholar. The data analysis technique used is the content analysis method which is divided into three stages, namely data presentation, data reduction, and conclusions. The research results reveal that the independent curriculum aims to clear the minds of teachers and students and humanize those who work in the field of education. Humanistic learning theory emphasizes students' freedom in self-realization. Students' talents, interests and abilities are optimized through meaningful learning. Teachers and students work together to determine methods, objectives, materials and assessments for the learning process.